The Correlation Between Vaginal Hygiene Practices and the Prevalence of Fluor Albus Among Pregnant Women at Tamangapa Health Center - Sartika Sartika; Nadyah Haruna; Dewi Setiawati; Rosdianah Rahim; Fatmawati Fatmawati (Journal of Public Health and Pharmacy, 2025)
Introduction: Flour albus, or vaginal discharge, affects reproductive health globally, including in Indonesia. It may be physiological or pathological, indicating an infection or another health issue. Pregnancy hormones increase the risk of flour albus; therefore, vaginal hygiene is crucial. However, many pregnant women lack information on hygiene, increasing their risk of pathological disorders. This study investigates the association between vaginal hygiene and flour albus in pregnant women undergoing ANC at Tamangapa Health Centre, a topic that has been rarely studied. Methods: This study employed a cross-sectional design using a quantitative approach. A total of 52 pregnant women in their second and third trimesters were recruited through incidental sampling during ANC visits. Ethical approval and informed consent were obtained prior to data collection. Data were gathered through questionnaires and vaginal discharge examinations. Analyses included univariate, bivariate, and multivariate methods, with the Mann-Whitney Test used for statistical significance. Results: The findings revealed that 37 respondents experienced physiological fluor albus despite adhering to appropriate vaginal hygiene practices. Statistical analysis showed a significant correlation between vaginal hygiene and the type of fluor albus, with a p-value of 0.000 (p < 0.005). Conclusion: The study stresses the need for vaginal hygiene in pregnant women to prevent pathological leukorrhea. Vaginal care education reduces complaints and improves reproductive health. This research has major implications for public health policy, particularly in prenatal care, to raise awareness and improve hygiene. It can also help build community-based preventive programs and integrate vaginal hygiene education into antenatal care to lower reproductive health risks.